Women Empowerment and its Challenges in Kerala-India: A Perspective of Madzhab al-Shafi'i Islamic Teachings - Abubakar Muhammad, Adamu; Khan, Huma; Abubakar Shariff, Ikilima; Apriantoro, Muhamad Subhi (Universitas Muhammadiyah Surakarta, 2024)
This paper examines the perspective of Madzhab al-Shafi'i's Islamic teachings on the challenges of women's empowerment in Kerala, India. It discusses the current socio-economic and legal issues affecting women's empowerment, and the impact of traditional gender roles and cultural norms on this progress. The study employs both qualitative and quantitative methods to review related literature and identify the various legal and cultural barriers women in Kerala face in their quest for equal rights and opportunities. Additionally, it includes semi-structured interviews with prominent Islamic scholars, women professionals, and government officials to analyze how Madzhab al-Shafi'i's teachings could address these challenges. The findings indicate that Madzhab al-Shafi'i's teachings have significant potential to transform Kerala's culture of inequality. Furthermore, these teachings could help bridge the gender gap by promoting mutual respect and understanding. In conclusion, the paper offers valuable insights into the dynamics of gender justice in Kerala and the potential of Madzhab al-Shafi'i's teachings to foster a more equal and just society. It suggests that Madzhab al-Shafi'i's writings should be considered when developing strategies to promote and sustain women's empowerment in such contexts.